PREDIKSI PERINGKAT OBLIGASI DENGAN CORPORATE GOVERNANCE PERCEPTION INDEX (CGPI) DAN KARAKTERISTIK OBLIGASI - Gunarsih, Tri; Prasasti, Ponco Adityia; Sari, Septi Diana (University of Merdeka Malang, 2015)
The objective of this study was to predict the impact of Corporate Governance Perception Index (CGPI) andBond Characteristics to Bond Rating by using the ordinal logistic regression. This regression was used sincethe dependent variable was ordinal data, consisting of three groups. The CGPI issued by Indonesian Instituteof Corporate Governance (IICG) was a score from 0 to 100 while the characteristics of the bond consisted ofthree variables, namely subordinated bonds, industry type and the maturity of the bond. The results of thisstudy indicated that scores of CGPI, subordinated bonds and the type of the industry were statistically significantat ?5%while the maturity of the bond was not. The positive direction of the relationship between scores ofCGPI to bond rating suggested that the higher the score, the higher the rating. The negative sign of subordinatedbonds suggested that subordinated bonds had a rating lower than non-subordinated bonds. The lastsignificant variables, type of industry suggested that financial and utility industry had higher bond ratingfrom other industries.